2017
DOI: 10.1002/2016jg003331
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of physical and biogeochemical processes to phytoplankton biomass enhancement in the surface and subsurface layers during the passage of Typhoon Damrey

Abstract: In this study, a one‐dimensional physical‐biogeochemical coupled model was established to investigate the responses of the upper ocean to Typhoon Damrey in the basin area of the South China Sea. The surface chlorophyll a concentration (Chl a) increased rapidly from 0.07 to 0.17 mg m−3 when the typhoon arrived and then gradually reached a peak of 0.61 mg m−3 after the typhoon's passage. The subsurface Chl a decreased from 0.34 to 0.17 mg m−3 as the typhoon arrived and then increased gradually to 0.71 mg m−3. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 59 publications
1
13
0
Order By: Relevance
“…The decreasing in SST is a general pattern; in comparison, the typhoon induced variation in chlorophyll is much more complex and varying in each case. Increasing in chlorophyll are found respective only around 50% and 18% of typhoons in the South China Sea (Pan et al, 2017) and northwest Pacific Ocean (Lin, 2012). This is at least due to the surface observations can only observe an elevation in chlorophyll if vertical mixing reaches DCM (Figure 2) or upwelling reaches the surface (Zhang et al, 2018).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The decreasing in SST is a general pattern; in comparison, the typhoon induced variation in chlorophyll is much more complex and varying in each case. Increasing in chlorophyll are found respective only around 50% and 18% of typhoons in the South China Sea (Pan et al, 2017) and northwest Pacific Ocean (Lin, 2012). This is at least due to the surface observations can only observe an elevation in chlorophyll if vertical mixing reaches DCM (Figure 2) or upwelling reaches the surface (Zhang et al, 2018).…”
Section: Discussionmentioning
confidence: 93%
“…CC BY 4.0 License. mixed layer (Letelier et al, 2004;Cullen 2015;Gong et al, 2017;Pan et al, 2017). The question then is whether the energy transfer from typhoons generates sufficient mixing to "break" through both the base of the wind-mixed layer as well as the deeper nutricline, thereby transfer new nutrients into the photic zone.…”
Section: Introductionmentioning
confidence: 99%
“…As the oscillations propagate downward into the seasonal thermoclines as near-inertial internal waves, vertical shears can form and cause shear instabilities that result in enhanced turbulent mixing and vertical diapycnal fluxes of nutrients and heat . Typhoon-enhanced surface water mixing resulting in ocean productivity has been seen in satellite data (Lin 2012;Lin et al 2003;Babin et al 2004;Siswanto et al 2007Siswanto et al , 2008 and numerical simulations (Shibano et al 2011;Menkes et al 2016;Pan et al 2017). showed that typhoon-generated near-inertial internal waves, propagating and breaking in the nutricline led to high export fluxes and high chlorophyll patches in the deep chlorophyll maximum layer.…”
Section: Introductionmentioning
confidence: 89%
“…Here, the wind-mixed layer comprises only the upper (shallow) portion of the sunlit and nutrient-depleted surface layer, with the former being much shallower than the latter (Du et al, 2017). In this case, the photic zone extends far below the typical wind-mixed layer, and a deep chlorophyll maximum (DCM) forms at the top of the nutricline and may exist at twice the depth of the wind-mixed layer or deeper (Letelier et al, 2004;Cullen 2015;Pan et al, 2017). The question then is whether the energy transfer from typhoons generates sufficient mixing to "break" through both the base of the wind-mixed layer and the deeper nutricline, thereby transferring new nutrients into the photic zone.…”
Section: Introductionmentioning
confidence: 99%